The Effect of Push Motivation, Pull Motivation and Islamic Norm Practice on Muslim Tourist Satisfaction and Destination Loyalty - ., Muchsin; ., Rahmaniar; Subhan , M. (Journal of Ecohumanism, 2024)
The purpose of this study was to determine the effect of Push Motivation, and Pull Motivation and Islamic Norm Practice on Muslim Tourist Satisfaction and Destination Loyalty in Lhokseumawe City. The research stages include: data observation, determining the main problem, activity objectives, literature study, data collection, data processing, analysis of results, and evaluation of research results. The results of the research push motivation has no significant positive effect on Muslim tourist satisfaction and on destination loyalty. push motivation has a significant positive effect on Muslim tourist satisfaction and on destination loyalty. Islamic norm practice has a significant positive effect on Muslim tourist satisfaction while Islamic norm practice has no significant positive effect on destination loyalty satisfaction.